Foreign direct investment, trade openness and environmental pollution in Pakistan: does renewable energy mitigate environmental degradation? - Huang, Xinbo; Ahmad, Waqar; Umair, Muhammad; Antohi, Valentin Marian; Fortea, Costinela; Cristache, Nicoleta (Frontiers in Environmental Science, 2025)
Environmental sustainability is a critical and urgent challenge of the modern world. Pakistan continues to struggle with balancing economic growth and environmental protection. In recent years, Pakistan has faced severe environmental issues, notably air pollution. This study investigates the impact of foreign direct investment (FDI) and trade openness on environmental pollution and examines how this relationship is moderated by renewable energy. Using Pakistan’s annual data from 1990 to 2022, the ARDL model and the Granger Causality technique employ for empirical analysis. The results indicate that FDI and trade openness increase environmental pollution in the short run and long run. Furthermore, the results reveal that renewable energy not only directly reduces environmental pollution but also significantly mitigates the negative environmental impacts of FDI and trade openness in both the short run and long run. Granger causality results further confirm that FDI, trade openness, and renewable energy consumption have a significant influence on environmental pollution, thereby reinforcing their predictive power. Furthermore, the results are validated through Dynamic OLS and Fully Modified OLS techniques. The findings support the Environmental Kuznets Curve (EKC) and Pollution Halo Hypothesis. However, these results underscore the crucial need for policies that strategically link FDI and trade openness with renewable energy policies to reduce environmental pollution while promoting economic development.